Enantiomeric recognition of α-amino acid derivatives by chiral uranyl–salen receptors. Issue 22 (27th May 2015) - Forte, Giuseppe; D'Urso, Alessandro; Ballistreri, Francesco P.; Toscano, Rosa M.; Tomaselli, Gaetano A.; Trusso Sfrazzetto, Giuseppe; Pappalardo, Andrea
Graphical abstract: Highlights: We synthesized two monotopic chiral uranyl–salen receptors1 and2 . We evaluated the enantioselective recognition towards selected α-amino acid salts. Excellent selectivity was obtained between d / l -Trp –TBA pair and the receptor2 . The tert -butyl groups in host2 are involved in the stabilization of the TBA cation. Abstract: Enantioselective molecular recognition of α-amino acid derivatives by two chiral uranyl–salen hosts was investigated by NMR data. The receptors differ for the presence of two tert -butyl groups in the salen backbone. The uranyl hosts have shown high binding constant values and excellent enantioselectivities for the selected guests (up to 100 for the tryptophan derivative).